Various factors affecting human performance in a computerised environment - Ang, Kah Eng (2015)
This project report brings the reader through a field study conducted to examine the various factors affecting human performance in an office work station. The first chapter presents an introduction to the field of study, providing the background and objectives of the project. The methodology and the scope and limitations of the study are mentioned. Further, an overview of the literature, including an introduction to the human performance model is also given. The next three chapters review on the literature done. Chapter 2 considers how the major senses of the human could affect performance. The senses discussed are visual, hearing and touch. Chapter 3 discuss the ways in which the design of computer equipments affect the performance of the human. The equipments reviewed include the monitor, the keyboard as well as selected pointing devices. Chapter 4 examines selective aspects of the environment that have effect on human performance. This includes both the physical and social aspects of the environment. Following, chapter 5 identifies the selected research issues that are of interest in the current study. Chapter 6 summarises the survey findings, as well as analysing the results. From the analysis, majority of the results obtained is in consistent with the literature reviewed. In addition, the team has identified the common physical discomforts experienced by the respondents. The correlations between these discomforts and the poor design of the workstation are also explored in this chapter. The concluding chapter gives an overall summary of the whole project and also provides some recommendations. With such, it is hoped that this report will put the reader in a better position to progress further in the field of ergonomics and human-computer interaction.